POTENSI PENGEMBANGAN AGROWISATA DI DESA PUNGGUNG LADING KECAMATAN PARIAMAN SELATAN KOTA PARIAMAN - Yolandri Shaumi _; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The purpose this research are: (1) Opportunities for Guava Development in Punggung Lading Village, South Pariaman District, Pariaman City (2) Inhibiting factors for the development of Agro-tourism in Punggung Lading Village, South Pariaman District Pariaman City (3) Agro-tourism Potential in Punggung Lading Village South Pariaman District Pariaman City.This research method uses descriptive qualitative research. Data collection techniques, namely by observation, interviews, and documentation. The results showed that the potential of agro-tourism in the backyard village, Pariaman City sub-district, pariaman city is: 1) the opportunity for developing guava in Punggung Lading village, Pariaman City sub-district, Pariaman city is very likely to be developed due to the absence of other adjoining agro-tourism objects, potential income and benefit the community, its strategic location. 2) The inhibiting factors for the development of agro-tourism are land acquisition that has not been completed due to inheritance, human resources that are not yet optimal and the weather is uncertain which results in decreased quality of guava fruit. 3) The potential of agro-tourism is commodity crops of guava, This area includes the area for cultivation of seasonal crops and good settlements to be developed.